Analisis Faktor-Faktor Yang Mempengaruhi Indeks Pembangunan - Murzan, Muhammad; Muhammad Effendi (PPJP ULM, 2019)
This research aims to find out information from the government, the wider community, economic growth and poverty together for the human development index in Banjarmasin City and which factors have the most influence on the human development index in Banjarmasin City. By using time series data in the period 2005-2016. The type of research used is quantitative descriptive using the linear regression method, the calculation data in this study using the SPSS program. data which is secondary data obtained from the Banjarmasin City Regional Finance Agency and the Banjarmasin City Central Bureau of Statistics The results obtained in this research are variables used for education, economic growth and poverty that are significant towards the human development index in the city of Banjarmasin. 91.9% of the independent variables in this study can explain the variables forming the human index in the city of Banjarmasin, while the remaining 8.1% by other factors outside the model. Variables from the government in the Health sector are the most dominant variables affecting the human development index in the city of Banjarmasin.